Psychological assistance to patients after laryngectomy - G. A. Tkachenko; S. O. Podvyaznikov; A. M. Mudunov; Е. V. Gusakova (Опухоли головы и шеи, 2020)
The study objective is to assess the effectiveness of psychological support to patients with laryngeal cancer after laryngectomy. Materials and methods.This study included 36 male patients aged between 45 and 62 years with morphologically verified stage II–IV (Т3–4N0–2М0) laryngeal cancer treated in the Department of Head and Neck Tumors, N. N. Blokhin National Medical Research Center of Oncology in 2011–2016. Patients were randomized into two groups. Group 1 included 14 patients who received antitumor therapy alone. Group 2 comprised 22 patients who additionally received psychological support. Patients’ mental state was assessed before treatment and 6 months after its completion using the Hospital Anxiety and Depression Scale and Symptom Check List-90 Revised. Two patients from Group 1 and 1 patient from Group 2 were excluded from the study at the first stage. Results. We found that patients in both groups had severe psychopathological symptoms (including depression, interpersonal sensitivity, and severe distress) six month after treatment completion (according to the Symptom Check List-90 Revised). Patients who received psychological support demonstrated higher level of depression than healthy controls, but it was still significantly lower than that in patients who received no psychological assistance. Similar results were obtained by the Hospital Anxiety and Depression Scale: patients who received psychological support had significantly lower level of depression than patients who had no psychological support (8.3 ± 0.9 vs 10.2 ± 0.6 points respectively). Conclusion. Patients with laryngeal cancer who received psychological assistance (including cognitive behavioral psychotherapy) demonstrated significantly lower level of depression 6 months after treatment completion compared to those who received no psychological support.